Is there still gender on the agenda for spatial planning theories? Attempt to an integrative approach to generate gender-sensitive planning theories. - Damyanovic, Doris; Zibell, Barbara (Routledge, 2013)
The objective of the article is to emphasise the importance of integrating a gender perspective in the planning sciences to advance planning theories. We will first debate how gender issues are integrated into planning practice and theory today. At the beginning we refer to the article of Sandercock and Forsyth "A gender agenda - new directions for planning theory" (1992). We will deal with the question of how gender issues are received in the European mainstream of handbooks on planning theory. Furthermore, we will discuss why and how gender perspectives are to be integrated into planning to bridge the gap between gender-sensitive and mainstream approaches to planning theory. We outline why gender planning has to be an integrative planning approach by linking to the integrative approaches of Mitchell (2008, 2009) and Wilber (2001, 2011). In particular, we want to highlight that integrative thinking is a basic idea of gender planning. Furthermore, we describe how gender planning can be a catalyst for valuable integrative approaches in planning which, up to hitherto, have been less recognised than the mainstream approaches.
Keywords: Raumplanung; Stadtplanung; Planungstheorie; Planungspraxis; Geschlecht; Verwaltungshandeln; Genderperspektive; Gender Mainstreaming; Planungswissenschaft